Domestic Violence against Women: A Qualitative Study in Assam - Bharati, Sangita (International Journal of Psychosocial Rehabilitation, 2020)
Domestic violence (DV) against women, married as well as unmarried, is widely prevalent across India. Various socio-cultural factors are associated with perpetuation of domestic violence. This study aims at understanding the context of DV in Assam, a state from India’s North-East region. The study is a qualitative one and conducted using primary data. Interviews with victims are conducted and observations have been done in shelter homes to gather necessary information. The finding reveals the different forms that domestic violence takes in Assam and how the issue is perceived by the victims. The issue of domestic violence is being attempted to understand in its socio-cultural context. The patriarchal social structure is found to provide the hotbed for emergence of DV against women.